Highly Conductive PEDOT:PSS Patterning through Conventional Photolithography using a Silver Interlayer and its application in ITO‐free OLEDs. Issue 1 (June 2014) - Ouyang, Shihong; Xie, Yingtao; Shi, Qiang; Cai, Shucheng; Zhu, Dalong; Xu, Xin; Wang, Dongping; Tan, Te; Fong, Hon Hang
Abstract PEDOT:PSS is a robust conductive polymer which is promising in future flexible applications. In order to integrate PEDOT:PSS into various devices, we introduce a simple patterning scheme for PEDOT:PSS. By using a silver interlayer, conventional photolithographic processes can be used. High resolution patterns and ITO‐free OLEDs are demonstrated.